STED Imaging the Dynamics of Lysosomes by Dually Fluorogenic Si‐Rhodamine. Issue 37 (27th May 2021) - Fan, Mengting; An, Haiyan; Wang, Chuanfeng; Huo, Shuhui; Wang, Ting; Cui, Xiaoyan; Zhang, Dazhi
Abstract: Super‐resolution microscopy (SRM) imaging of the finite subcellular structures and subtle bioactivities inside organelles delivers abundant cellular information with high fidelity to unravel the intricate biological processes. An ideal fluorescent probe with precise control of fluorescence is critical in SRM technique like stimulated emission depletion (STED). Si‐rhodamine was decorated with both targeting group and H + ‐receptor, affording the dually fluorogenic Si‐rhodamine in which the NIR fluorescence was efficiently controlled by the coalescent of spirolactone‐zwitterion equilibrium and PeT mechanism. The dually fluorogenic characters of the probe offer a perfect mutual enhancement in sensitivity, specificity and spatial resolution. Strong fluorescence only released in the existence of targeting protein at acidic lysosomal pH, ensured precisely tracking the dynamic of lysosomal structure and pH in living cells by STED. Abstract : Finite subcellular structures and subtle bioactivities in the living cells are essential to understand biological processes. Super‐resolution microscopy (SRM) is a powerful tool to visualize cellular structures and bioactivities at the nanometer scale. However, synthesizing elaborate probes with outstanding photostability, accurate positioning, reliable selectivity, high brightness is extremely intricate and challenging, especially for SRM bioimaging. In this newly developed probe, strong fluorescence was only realised in the existence of targeting protein at acidic lysosomal pH, ensuring reliable tracking of the dynamics of lysosomal structure and pH in living cells by STED.